ANALISIS PENURUNAN LAJU PRODUKSI SUMUR PANAS BUMI LAPANGAN X MENGGUNAKAN METODE SPIVEY - Ahmad Nur Febryansyah; Saputri, Eriska; Tongkeles, Patriks (Universitas Jember, 2026)
Geothermal energy is a strategic renewable resource for Indonesia, yet maintaining production levels is critical for energy security. This research aims to analyze the production decline of Well XY in Field X and forecast future flow rates to ensure sustainable power plant operations. The study utilizes a quantitative descriptive method, employing the Spivey Decline Curve Analysis (DCA) approach and the Gauss-Jordan reduction method for data regression. Results indicate that the decline is significantly influenced by operational steam losses at the rock muffler and cooling tower. The analysis calculated a loss rate parameter (b) of 0.053, with the regression model demonstrating high accuracy relative to actual production data. Forecasts suggest that Well XY’s production will decline to 11.23 t/h by December 2025 if no technical interventions are implemented. In conclusion, the Spivey method provides a reliable projection for reservoir management, highlighting the necessity of operational adjustments to prevent steam supply shortages.